2010
DOI: 10.2196/jmir.1538
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Informatics Techniques for Processing and Analyzing Web Blogs of Military Service Members

Abstract: IntroductionWeb logs (“blogs”) have become a popular mechanism for people to express their daily thoughts, feelings, and emotions. Many of these expressions contain health care-related themes, both physical and mental, similar to information discussed during a clinical interview or medical consultation. Thus, some of the information contained in blogs might be important for health care research, especially in mental health where stress-related conditions may be difficult and expensive to diagnose and where ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Equally interesting, is how the US military has used natural language processing (where computers evaluate meaning) to automatically filter and retrieve information on blog posts by military servicemen as a means to monitor emotions and posttraumatic stress disorder after operational deployment [39]. …”
Section: Resultsmentioning
confidence: 99%
“…Equally interesting, is how the US military has used natural language processing (where computers evaluate meaning) to automatically filter and retrieve information on blog posts by military servicemen as a means to monitor emotions and posttraumatic stress disorder after operational deployment [39]. …”
Section: Resultsmentioning
confidence: 99%
“…The authors used manual annotation for generating training data and used word n-grams as features, while refining features using text mining techniques such as principal component analysis (9). Konovalov et al (10) developed a classifier using manually selected relevant word unigrams as features to extract combat exposure descriptions from Weblogs. Yang et al (11) reported best performing information retrieval metrics for detecting adverse drug events from user-contributed content in social media.…”
Section: Introductionmentioning
confidence: 99%
“…The model could predict disease activity in real-time [4]. As an exemplar, mining the blogs of military personnel involved in operation enduring freedom in Iraq, was able to discern the emotional tone of blogs and detect service personnel experiences and emotional reactions to combat exposure [5]. This further highlights the potential applicability of machine learning to psychiatric clinical and research settings [6].…”
Section: Related Backgroundmentioning
confidence: 88%